Skill Development in Middle Level Occupations: The Role of Apprenticeship Training - Robert I. Lerman (Institute for the Study of Labor (IZA), 2013)
Concerns about the polarization of the labor market are widespread. However, countries vary widely in strategies for strengthening jobs at intermediate levels of skill. This paper examines the diversity of approaches to apprenticeship and related training for middle-level occupations. We begin by defining and describing middle-skills occupations, largely in terms of education and experience. The next step is to describe skill requirements and alternative approaches to preparing and upgrading the skills of individuals for these occupations. Programs of academic education and apprenticeship programs emphasizing work-based learning have often competed for the same space but the full picture reveals significant numbers of complementarities. Third, we consider the evidence on the costs and effectiveness of apprenticeship training in several countries. The final section highlights empirical and policy research results concerning the advantages of apprenticeship training for intermediate level skills, jobs, and careers.
Keywords: J23; J24; I21; 330; training; apprenticeship; skills; Betriebliche Ausbildung; Fachkräfte; Anforderungsprofil; Kosten-Nutzen-Analyse; Welt; USA